Research progress in the origins of myofibroblasts in skin fibrotic diseases - Xianzhong ZHU; Peijun MAI; Yanghai WEI; Maoyun WEI; Chuangye QIU; Peiran ZHANG; Qing QI (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Typical skin fibrotic diseases include hypertrophic scar, keloid and scleroderma. These diseases characterized by excessive activation of myofibroblast, and abnormal deposition of extracellular matrix can lead to permanent scarring and organ dysfunction, and seriously affect the physical and mental health of patients. Myofibroblasts play a central role in skin fibrotic diseases. Current studies have shown that fibroblasts, endothelial cells, pericytes, macrophages and other cells can be transformed into myofibroblasts after induction by multiple factors such as pro-fibrotic mediators, activation of signaling pathways related to skin fibrosis, changes in morphological and biochemical characteristics, and expression of myofibroblast markers, including α-smooth muscle actin (α-SMA). Targeting these cell transformation processes is expected to be a new therapeutic strategy for regulating the progression of skin fibrotic disease. Therefore, this review will focus on the progress of the origins of the myofibroblasts in skin fibrotic diseases.